Effects of incorporating germinated brown rice on the antioxidant properties of wheat flour chapatti - Singh Gujral, H.; Sharma, P.; Bajaj, R.; Solah, Vicky (Sage Publications, 2012)
Brown rice after germinating for 24 and 48 h was milled into flour and incorporated in whole wheat flour at a level of 10% to prepare chapattis. The objective was to use chapatti as a delivery vehicle for germinated brown rice. The flour blends and chapattis made from the flour blends were evaluated for their antioxidant properties. Incorporating germinated brown rice flour increased the total phenolic content of the flour blend from 1897 to 2144 µg FAE/g. The total flavonoids content increased significantly from 632.3 to1770.9 µg CAE/g and metal chelating activity significantly increased by 71.62%. Antioxidant activity increased significantly by the addition of brown rice flour and addition of 24- and 48-h germinated brown rice flour further increased the antioxidant activity significantly. The total phenolic content and total flavonoids content decrease significantly in all the blends after baking the flour into chapatti. A decrease of 3% to 29% was observed in the total phenolic content and a decrease of 25% to 42% was observed in the total flavonoids content. However, baking of the flour blends into chapatti increased the reducing power, metal chelating activity by three folds and antioxidant activity from 64% to 104%.